(1450) A comparative analysis of some methods for solving quadratic programming problems تحليل مقارن لبعض طرق حل مسائل البرمجة التربيعية - Zaghloul, Fathia; Zolfa, Shalabi (The Institute of National Planning, 2018)
The problem of quadratic programming is that of minimizing a convex function subject linear constraints. It is one of the simplest cases of nonlinear programming.